Stretch-induced structural evolution of pre-oriented isotactic polypropylene films: An in-situ synchrotron radiation SAXS/WAXS study. (1st February 2021) - Habumugisha, Jean Claude; Feng, Shengyao; Iqbal, Obaid; Lin, Yuanfei; An, Minfang; Meng, Lingpu; Wang, Daoliang; Chen, Wei; Li, Liangbin
Abstract: In-situ small- and wide-angle X-ray scattering (SAXS/WAXS) is employed to study the stretch-induced structural evolutions of four different pre-oriented isotactic polypropylene (iPP) cast films during uniaxial stretching at room temperature. The mechanical properties and structural evolutions show distinct features with the improvement in orientation of initial structure. For low-oriented films, the tensile stress induces the amorphization of lamellar crystals parallel to stretching direction, while the shear stress triggers the shearing of lamellar stacks at other angles through crystal slipping. For high-oriented films, the elastic deformation mode dominates as the normals of all lamellae are along stretching direction. Under tensile stress, micro-buckling or bending replaces the lamellar shearing to trigger the initial deformation instability of crystals. And stress-induced amorphization of lamellar crystals might also occur at large strains in the strain hardening zone. This study uncovers the different structural evolution roads of low- and high-oriented films, which will aid to deepen the understanding of the orientation effects on the deformation mechanisms of other semi-crystalline polymers. Graphical abstract: Image 1 Highlights: The structural evolutions of pre-oriented iPP films during tensile deformation are proposed. The pre-orientation of iPP films plays an important role on the deformation mechanism. The coupled effects of tensile and shear stress are considered for low-oriented films. Elastic deformation mode under effect of tensile stress dominates for high-oriented films.